2018
DOI: 10.3892/etm.2018.6506
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the disease module associated with osteosarcoma via a network‑ and pathway‑based approach

Abstract: Osteosarcoma is the most common type of primary malignant bone tumor observed in children and adolescents. The aim of the present study was to identify an osteosarcoma-related gene module (OSM) by looking for a dense module following the integration of signals from genome-wide association studies (GWAS) into the human protein-protein interaction (PPI) network. A dataset of somatic mutations in osteosarcoma was obtained from the dbGaP database and their testing P-values were incorporated into the PPI network fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Overexpression of IKZF1 can activate autoimmune susceptibility through infiltrating NKG2D+ and CD8+ T cells ( Chen et al, 2018a ). Its prognostic value has been noted in osteosarcoma ( Zhang and Yang, 2018 ). JCHAIN encodes the immunoglobulin J chain and links monomer units of IgA and IgM, and the upregulation of JCHAIN was likely related to tumor aggression, as studied in a cohort of patients with acute lymphoblastic leukemia (ALL) who had died ( Tomar et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of IKZF1 can activate autoimmune susceptibility through infiltrating NKG2D+ and CD8+ T cells ( Chen et al, 2018a ). Its prognostic value has been noted in osteosarcoma ( Zhang and Yang, 2018 ). JCHAIN encodes the immunoglobulin J chain and links monomer units of IgA and IgM, and the upregulation of JCHAIN was likely related to tumor aggression, as studied in a cohort of patients with acute lymphoblastic leukemia (ALL) who had died ( Tomar et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the exploration of downstream targets in the previous study [29] , we dug into the regulation mechanism of miR-451a on the oncogenic AKT/mTOR signaling pathway in osteosarcoma. Through western blot analysis of AKT/mTOR pathway related proteins, we found that miR-451a inhibits the AKT/mTOR signaling pathway via PDPK1 which was previously reported as a potential diagnostic biomarker for osteosarcoma [30] and a tumor-propeller in osteosarcoma [24] . Further, we uncovered that miR-451a suppresses the AKT/mTOR signaling pathway via PDPK1-induced phosphorylation of AKT at Thr308 site through q-PCR analysis, Co-IP assay and in vitro phosphorylation experiment.…”
Section: Discussionmentioning
confidence: 76%
“…It is a precursor of amyloid beta that contributes to producing amyloid plaques found in the brains of Alzheimer’s disease patients. APP is also reported as one of the diagnostic biomarkers for OS ( Zhang and Yang, 2018 ), and its high expression reduces the survival of OS patients but not pan-cancer patients. Taken together, APP can be a druggable target, selective to OS, and PCOLCE is one of its biological blockers.…”
Section: Discussionmentioning
confidence: 99%